Energy-efficient DRX scheduling for D2D communication in 5G networks. (15th August 2018) - Liang, Jia-Ming; Chang, Po-Yen; Chen, Jen-Jee; Huang, Chien-Feng; Tseng, Yu-Chee
Abstract: In recent years, intelligent devices such as smart phones and smart tablets are grown and developed rapidly. High-bandwidth media services such as live streaming, gaming and multi-user video conferencing are more and more popular. This results in spectrum resource depletion of the cellular network. To alleviate the problem, the 3rd Generation Partnership Project (3GPP) has proposed a new technology, called device-to-device (D2D) communications . However, D2D devices and direct link cellular users all share and access the same spectrum resource, thus degrading the network performance significantly due to the interference. In addition, due to the frequent communication nature of streaming and gaming services, the power consumption of devices is increasing dramatically. To mitigate above problems, this paper investigates how to improve the spectrum efficiency by well scheduling and allocating radio resource to more concurrent D2D and cellular users on the uplink direction and reduce unnecessary power consumption of devices via Discontinuous Reception (DRX) scheduling while guaranteeing users' Quality of Service (QoS) . We propose an energy-efficient resource and sleep scheduling scheme. This scheme first establishes a conflict graph to maintain the transmission and interference relationship, and then tries to maximize concurrent D2D and mobile users by resource reuse. At the same time, the method also exploits DRX technology to further decrease possible interference and conserve devices' power consumption through optimizing their sleep operation. Simulation results show that our scheme can achieve better performance on system throughput, network capacity, and power saving compared to the existing schemes.